Kaśka Kariatyda już tu nie mieszka. Temat niechcianej ciąży i aborcji w nowej prozie kobiet - Nowacki, Dariusz (Postscriptum Polonistyczne, 2020)
The article discusses the literary representations of the experience of unwanted pregnancy and abortion in new women’s prose. The author of the article refers to the novels published between 2003 and 2016. He considers the previously conducted research on the same subject (especially that of Agnieszka Mrozik). However, he concentrates mainly on the prose created in the last few years. He is above all interested in changes regarding the problem of unwanted pregnancy and abortion that occurred after 1989. When writing about this aspect of female experience has appeared in new prose, it is usually about the past and used to question the morality of the Polish People’s Republic. Recently the problem of unwanted pregnancy seems to be non‑existent as all issues pertaining to maternity are solved in a similar way: despite initial hesitations the heroines of the novels decide to have babies and never regret their choice. In this context Aleksandra Zielińska’s novel Przypadek Alicji (The case of Alice) seems to be especially interesting. Considerations concerning this novel appear in the final part of the article.